Optical characterization of hafnium oxide thin films for heat mirrors. (April 2015) - Ramzan, M.; Rana, A.M.; Ahmed, E.; Wasiq, M.F.; Bhatti, A.S.; Hafeez, M.; Ali, A.; Nadeem, M.Y.
Abstract: HfO2 thin films (80 nm) fabricated at various substrate temperatures (25–120 °C) using an electron beam evaporation technique and thermally annealed at 500 °C were characterized through X-ray diffraction, atomic force microscopy and UV–vis–NIR spectroscopy. X-ray diffraction results illustrate that as-deposited HfO2 films are amorphous, which transform to polycrystalline (monoclinic) structure on annealing. Films reveal various morphologies and crystallite orientations, which seem to be responsible for variations in surface roughness (5–12 nm), mean crystallite size (5.2–6.3 nm), refractive index (1.43–1.79), extinction coefficient (0.066–0.103) etc. In addition, better reflectivity (5–10%) of annealed HfO2 films in near infrared (NIR) region has been improved by inserting a metallic Ag layer to form insulator-metal-insulator structure useful for heat mirror applications. Optical characterization of such HfO2 (10 nm)/Ag(5 nm)/HfO2 (10 nm) structure illustrates minimum transmittance ( 35%) in the visible region and maximum reflectance ( 90%) in the visible (vis) and near infrared regions.